The Effectiveness of Skill Training Model for Increasing the Street Children’s Competence to Get a Job - Murhadi, Murhadi (Humaniora, 2018)
This research was based on the importance of the effectiveness of skills training for street children as a solution to reduce their activity of begging money on the street. Referring to the problem, there were two objectives in this study. First, it was to obtain an overview of the skill training conditions undertaken by street children in Depok as the multi-location test and Tangerang Selatan as the main research location. Second, it was to know the effectiveness of the implementation of skills training in improving the competence of street children to get a job. Several theories and concepts were used as the reference in the implementation of this study. The method was Research and Development (R&D) and quasi-experimental approach. Data were collected through participant observation, documentation, interview, questionnaire, and group discussion. The results of this research show that effective training can provide skills for street children to get a job.